Disability and quality of life in patients with treatment-resistant schizophrenia on long- term clozapine therapy - Dhandapani Nandakumar; Ragul Ganesh; Koushik S. Deb; Raka Jain; Mamta Sood (Indian Journal of Psychiatry)
Objectives: To assess disability and quality of life (QOL) in treatment resistant schizophrenia (TRS) on long term clozapine therapy and assess their correlation with positive, negative and cognitive symptoms. Methodology: Disability and QOL in forty patients with TRS (as per modified Kane’s criteria) were assessed using World Health Organization Disability Assessment Schedule 2.0 and World Health Organization Quality of Life–BREF. Scale for assessment of positive symptoms, scale for assessment of negative symptoms and Addenbrooke’s cognitive examination-III were used to assess positive, negative and cognitive symptoms. Medication adherence rating scale assessed medication adherence. Results: Disability and QOL correlated significantly with medication adherence, negative and cognitive symptoms but not with positive symptoms. Subgroup analysis revealed significant difference between medication adherence (good vs poor) and cognitive (impairment vs non-impairment) groups. Conclusion: Negative and cognitive symptoms, and medication adherence correlated with disability and QOL.